#### Answer

$-i$

#### Work Step by Step

$\frac{1}{i}=\frac{1(-i)}{i(-i)}=\frac{-i}{-i^{2}}=\frac{-i}{-(-1)}=\frac{-i}{1}=-i$

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$-i$

$\frac{1}{i}=\frac{1(-i)}{i(-i)}=\frac{-i}{-i^{2}}=\frac{-i}{-(-1)}=\frac{-i}{1}=-i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.